Stable Gastric Pentadecapeptide BPC 157 and Wound Healing - Seiwerth, Sven; Milavic, Marija; Vukojevic, Jaksa; Gojkovic, Slaven; Krezic, Ivan; Vuletic, Lovorka Batelja; Pavlov, Katarina Horvat; Petrovic, Andrea; Sikiric, Suncana; Vranes, Hrvoje; Prtoric, Andreja; Zizek, Helena; et al. (Frontiers in Pharmacology, 2021)
Significance. The antiulcer peptide, stable gastric pentadecapeptide BPC 157 (used to be in ulcerative colitis trials, and now for multiple sclerosis, no reported toxicity (LD1 not achieved)) is reviewed, focusing on the particular skin wound therapy, incisional/excisional wound, deep burns, diabetic ulcers, and alkali burns, that may be generalized to the other tissues healing. Recent Advances. BPC 157 has practical applicability (given alone, with the same dose range, and same equipotent routes of application, regardless the injury tested). Critical Issues. By simultaneously inducing the healing of the skin wound and other corresponding tissues wounds (colocutaneous, gastrocutaneous, esophagocutaneous, duodenocutaneous, vesicovaginal, rectovaginal) in rats. Healing of the wounds is accomplished by resolution of all 4 major events (vascular constriction, loose platelet plug, fibrin mesh to insure stability of platelet plug, dissolution of the clot). Thereby, BPC 157, is effective in wound healing much like it is effective in counteracting bleeding disorders, produced by amputation, and/or anti-coagulants application. Likewise, BPC 157 may prevent and/or attenuate or eliminate, thus, counteract both arterial and venous thrombosis. Then, the recovering effect it has on occluded vessels, bypassing the occlusion, appears as the specific effect of BPC 157 in ischemia/reperfusion. Future Directions. BPC 157 rapidly increases various genes expression in rat excision skin wound. This would define the healing in the other tissues, i.e., gastrointestinal tract, tendon, ligament, muscle, bone, nerve, spinal cord, cornea (maintained transparency), and blood vessels, seen with BPC 157 therapy.